1998
DOI: 10.1242/jcs.111.7.897
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cytokines on mycobacterial phagosome maturation

Abstract: One of the major mechanisms permitting intracellular pathogens to parasitize macrophages is their ability to alter maturation of the phagosome or affect its physical integrity. These processes are opposed by the host innate and adaptive immune defenses, and in many instances mononuclear phagocytes can be stimulated with appropriate cytokines to restrict the growth of the microorganisms within the phagosomal compartment. Very little is known about the effects that cytokines have on phagosome maturation. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(10 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…To further address the relevance of these findings in a whole animal model, we vaccinated neonatal WT or KO pups with BCG. Although BCG is an attenuated strain of Mycobacterium bovis and does not cause disease in immune-competent children, BCG is capable of similar phagolysosomal resistance as MTB ( Via et al., 1998 ). Persistence of vaccine antigen has been shown to drive effector responses ( Orme 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…To further address the relevance of these findings in a whole animal model, we vaccinated neonatal WT or KO pups with BCG. Although BCG is an attenuated strain of Mycobacterium bovis and does not cause disease in immune-competent children, BCG is capable of similar phagolysosomal resistance as MTB ( Via et al., 1998 ). Persistence of vaccine antigen has been shown to drive effector responses ( Orme 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…1b). Maximum activity was observed at pH 5.4, the pH corresponding to matured phagosomes of activated macrophages 21,22 . Reporter activity was diminished in highly acidic culture media (pH < 5), albeit remained above baseline.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that immune-activation of murine bone marrow derived macrophages with IFN-γ and/or LPS releases the arrest of phagosome maturation by mycobacteria [167,168]. TDM coated beads are capable of slowing down phagosome maturation, thus suggesting that TDM is contributing to mycobacterial survival in bone marrow-derived macrophages; TDM effect is abolished in immune-activated (by IFN-γ and/or LPS) wild-type, but not in activated nitric oxide synthase deficient macrophages.…”
Section: Phagosomes and The Role Of Nomentioning
confidence: 99%